Analysis of the solvency of companies with currency mismatches in the industrial sector of the Mexican Stock Exchange - José Antonio Morales Castro (RAN, 2019)
The article aims to analyze the behavior of the solvency rates of companies with monetary mismatches of the industrial sector of the Mexican Stock Exchange (BMV) during the exchange variations of 2007-2017. Six financial multiples were used to measure solvency, the data for its calculation were obtained from ECONOMÁTICA, the Mexican Stock Exchange and Banco de México. Using also the foreign currency debt index, the price of the dollar and the coding of the depreciation and appreciation of the Mexican currency, a logistical regression was developed, in which two groups of companies were established: (1) with exchange rate losses and (2) without foreign exchange losses. We found that solvency levels in companies that had foreign exchange losses did not deteriorate during the depreciation episodes of the Mexican currency. The variables that statistically managed to explain why companies take foreign exchange losses were: currency volatility, the price of the dollar, and the level of foreign currency debts.